Exploring the Perception Differences and Influencing Factors of Ecosystem Services Among Residents in Northeast China Tiger and Leopard National Park - Huiyan Qin; Han Wang; Panwar Rajat (Land)
Local residents’ satisfaction plays a crucial role in the successful management of national parks. However, limited attention has been paid to residents’ preferences in the management of national parks, which hinders the sustainable development and optimization of management systems. To address this gap, we focused on the Dongning area of Northeast China Tiger and Leopard National Park (NCTLNP) as a case study and employed the importance–performance analysis (IPA) framework to assess residents’ perceptions and cognitive rankings of current ecosystem services. Additionally, we examined how demographic and socio-economic factors influence these perceptions. Our findings reveal that local residents prioritize ecosystem services that directly impact their livelihoods and that their material, social, spiritual, and cultural needs are not fully met. Satisfaction and importance ratings varied across regions, with significant influences occurring from the residents’ sex, occupations, and livelihoods. Based on these results, we recommend strengthening the institutional framework for national park management and enhancing the scientific effectiveness of management policies by incorporating residents’ perspectives into decision-making processes.